Costs of post abortion care in Lima, Peru hospitals - Orozco, Luis Távara (2013)
Objectives: To determine care costs of incomplete abortions at public hospitals and elective abortions at a private institution. Design: Prospective study. Participants: Women with incomplete abortion. Methods: In 120 women with either complicated or non-complicated incomplete abortion in four public hospitals and 40 women in a private hospital, time for attention, cost of personal, drugs, materials, equipments and hospital functioning were determined; also pocket cost, transportation, children and home care and non-perceived income. All women signed informed consent. Main outcome measures: Care costs. Results: Hospital stay at three hospitals for non-complicated incomplete abortion until discharge was about 6 hours, more in one hospital because of internal norms. Abortion complications at the four hospitals required longer stay. Women with elective abortion required half the time of those with non-complicated incomplete abortion at hospitals. Total cost for non-complicated incomplete abortions care was similar at the four hospitals, between US$ 110 and US$ 150, and for complicated abortions between US$ 376 and US$ 858. Elective abortions care total cost was similar to that of non-complicated abortions care at hospitals. Conclusions: Non-complicated abortion stay of women was relatively short at hospitals. Complicated and non-complicated abortions care demanded an important cost for hospitals and women themselves. Elective abortion costs were accesible to every woman and none had complications. Key words: Abortion care costs, unsafe abortion, safe abortion.